2012
DOI: 10.1155/2012/385271
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Figure Recognition: Agreement among Pathologists and Computerized Detector

Abstract: Abstract. Despite the prognostic importance of mitotic count as one of the components of the Bloom -Richardson grade [3], several studies [2, 9, 10] have found that pathologists' agreement on the mitotic grade is fairly modest. Collecting a set of more than 4,200 candidate mitotic figures, we evaluate pathologists' agreement on individual figures, and train a computerized system for mitosis detection, comparing its performance to the classifications of three pathologists. The system's and the pathologists' cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 11 publications
0
55
0
Order By: Relevance
“…Due to its importance, a number of automated detectors have been designed to solve the problem [5,7,8,10,11].…”
Section: Related Work Mitosis Detection In Histology Images Stained Withmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to its importance, a number of automated detectors have been designed to solve the problem [5,7,8,10,11].…”
Section: Related Work Mitosis Detection In Histology Images Stained Withmentioning
confidence: 99%
“…Mitosis detection therefore represents a challenging visual pattern recognition task. In evaluating (on a large, non-public dataset) the agreement among different pathologists faced with this task, Malon et al found that "the level of agreement of the pathologists ranges from slight to moderate", with "strong biases", which "suggest that different pathologists interpret grading guidelines differently" (cited from [8]). This finding is consistent to the observation of low agreement among different pathologists on the evaluation set of the MITOS dataset (Goerner et al, oral presentation at ICPR 2012, unpublished).…”
Section: Related Work Mitosis Detection In Histology Images Stained Withmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, several systems succeeded in analyzing morphology of cell nuclei on hematoxylin-eosin (HE) stained specimens. Researchers compete for accuracy to count mitotic cells [16][17][18]. Cosatto et al quantitatively graded nuclear pleomorphism on histological images [19].…”
Section: Introductionmentioning
confidence: 99%